2016
DOI: 10.1093/jamia/ocv192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an e-Prescribing interface redesign on rates of generic drug prescribing: exploiting default options

Abstract: Default options in health information technology exert a powerful effect on user behavior, an effect that can be leveraged to optimize decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…With the widespread use of electronic medical records and computerized order entry, a simple solution may be to direct a physician to select a generic name by limiting the medication options to generic nomenclature. These ‘default options’ have been shown to be effective at increasing rates of generic prescribing [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the widespread use of electronic medical records and computerized order entry, a simple solution may be to direct a physician to select a generic name by limiting the medication options to generic nomenclature. These ‘default options’ have been shown to be effective at increasing rates of generic prescribing [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consider the strategy of designating a desired behaviour as the default option (from which individuals can opt out), which has successfully increased participation of employees in retirement saving plans,2122 promoted energy conservation,23 and may explain large differences in organ donation consent rates across countries with different policies 24. Defaults have also been used to promote adherence to guidelines with patients dependent on ventilators25 and to increase prescribing of generic drugs 426…”
Section: Nudges Often Require Calibrationmentioning
confidence: 99%
“…Behavioural interventions directed at healthcare professionals seem especially promising given that clinicians increasingly take actions using electronic health records, so that decisions are tracked and nudges can be deployed via modifications to standardised workflows. For instance, setting prescription drugs to their generic equivalents by default, while allowing clinicians to easily opt out, increased the rate of generic prescribing from 40% to 96% in one month 4…”
mentioning
confidence: 99%
“…E-prescribing has also been associated with higher generic prescription-fill rates (Howard et al 2018). In fact, Malhotra et al (2016) found generic prescriptions more than doubled when clinical decision support systems defaulted to the generic drug.…”
Section: Background and Literature Reviewmentioning
confidence: 99%